Liposomal irinotecan (Onivyde): Exemplifying the benefits of nanotherapeutic drugs - Milano, Gérard; Innocenti, Federico; Minami, Hironobu (Cancer science, 2022)
Irinotecan is a topoisomerase inhibitor, widely used in treatment of malignancies including pancreatic ductal adenocarcinoma (PDAC) as part of the FOLFIRINOX regimen prescribed as a first‐line treatment in several countries. However, irinotecan has not been successfully introduced as a second‐line treatment for pancreatic cancer and few randomized clinical studies have evaluated its added value. Efficacy of liposomal irinotecan (nal‐IRI) combined with 5‐fluorouracil and leucovorin (5‐FU/LV) was reported in the phase III NAPOLI‐1 trial in metastatic PDAC following failure of gemcitabine‐based therapy. Several features of nal‐IRI pharmacokinetics (PK) could result in better outcomes versus nonliposomal irinotecan. Irinotecan is a prodrug that is converted to active SN‐38 by carboxylesterase enzymes and inactivated by cytochrome P450 3A4/3A5. SN‐38 is inactivated by UGT1A1 enzymes. Individual variations in their expression and activity could influence enhanced localized irinotecan activity and toxicity. Liposomal irinotecan exploits the enhanced permeability and retention effect in cancer, accumulating in tumor tissues. Liposomal irinotecan also has a longer half‐life and higher area under the concentration‐time curve (0–∞) than nonliposomal irinotecan, as the liposomal formulation protects cargo from premature metabolism in the plasma. This results in irinotecan activation in tumor tissue, leading to enhanced cytotoxicity. Importantly, despite the longer exposure, overall toxicity for nal‐IRI is no worse than nonliposomal irinotecan. Liposomal irinotecan exemplifies how liposomal encapsulation of a chemotherapeutic agent can alter its PK properties, improving clinical outcomes for patients. Liposomal irinotecan is currently under investigation in other malignancies including biliary tract cancer (amongst other gastrointestinal cancers), brain tumors, and small‐cell lung cancer. Liposomal encapsulation of chemotherapeutic agents can modify their pharmacokinetic properties to improve clinical outcomes for patients. Liposomal irinotecan (nal‐IRI) exemplifies the benefits of this technology, leading to enhanced antitumor activity without increases in toxicity versus nonliposomal irinotecan. While approved for use in metastatic pancreatic ductal adenocarcinoma that has progressed on gemcitabine treatment, nal‐IRI is also under investigation in various other malignancies, and could result in better outcomes for patients with these tumors.